Histopathology and Anticolon Cancer Effects of Turmeric Ethanolic Extracts in Wistar Rats - Dumomangi Dorcas, Simeon-Lancelot; Jireh Cosmas, Okolie Nnaemeka; Gborieneomie, Mac-Fiberesima; Onyije, Felix M. (European Scientific Journal, ESJ, 2021)
Colon cancer is cancer that begins in the large intestine. It usually begins as small, non cancerous clumps that form inside the colon. It typically affects older adults and can occur at any age. The aim of this study is to investigate the histopathological changes of the colon of rats experimentally induced with cadmium chloride as well as the anticancer effect of the ethanolic extract of Curcuma longa. Thirty six healthy albino rats of both sexes were classified into six groups with each group comprising of five rats as follows ; group I: normal control rats, group 2: Cadmium Chloride induced rats, group 3: Aduracil-5 fluorouracil treated rats, Group 4: dimethyl sulfuroxide treated rats, groups 5 and 6 rats were treated with 875mg/kg and 437.5mg/kg of Curcuma ethanolic extracts respectively after initial induction of cancer with cadmium chloride. Comparative observation of the cadmium induced colon showed histopathological damage as evidenced by empty goblet cells, lacerated and suppressed mucosa, destruction of the surface epithelium, features which were lacking in the control and Curcuma longa treated colon. Curcuma treated colon exhibited marked improvement of the histomorphology whilst cadmium treated colon clearly showed tumor cells, cancer cells or invasive inflammatory cells. Adruracil-5fluorouracilan established anti colon cancer drugs treated colon showed mild improvement in the histomorphology of the colon while the dimethyl sulfuroxide treated colon revealed an insignificant impact. The ameliorative effect on rat colon occasioned by administration of Curcuma ethanolic extract suggests that the plant product may have therapeutic activity against colon inflammation in albino rats.